The old success [compact disc, unabridged] - Grimes, Martha (Grimes, Martha. Richard Jury mystery., 2019)
When a beautiful tourist washes up on a wild inlet, inspector Richard Jury finds himself looking at a murder that's very similar to two other unsolved cases.